Implementation of Human Resource Planning in Increasing the Productivity of Village Owned Enterprises in Lambar Village, Tigapanah District, Karo Regency - sitepu, Jupianus sitepu; Ananda, Feri (JURNAL REGIONOMIC, 2023)
BUMDes is an organization engaged in the village economy that can help and provide services to the community, and in its activities not only aim at financial gain, but also aim to support the improvement of community welfare. Especially businesses that can take advantage of the potential of natural resources and human resources and assets owned by the village. The results of the study show that not all BUMDes in Tigapanah District can be managed properly, even though the purpose of their formation is to improve people's welfare. Based on the results of interviews and observations as well as the documents that the researchers managed to collect, there were several obstacles encountered in the management of BUMDes. The policy implementation model that will be used in this study is the policy implementation model according to Van Meter and Van Horn. The Van Meter and Van Horn models in principle are that policy implementation takes place in a linear fashion from public policy, policy implementers, and policy performance. In organizational strategy it is suggested to prioritize programs that will be created by looking at the vision and mission that have been sparked so that what is the goal of BUMDes can be achieved in the future, the resource strategy prioritizes the provision of appropriate training to the community and also the management of facilities and infrastructure is further improved, the procurement of which is more important so that the community can use it properly and the programs that are developed look more at businesses or programs that provide a significant impact on BUMDes and also the community in the form of businesses in the agricultural sector in order to create BUMDes sustainability in the midst of society.